PAYROLL INFORMATION SYSTEM AT PT. USING VISUAL AMDAH INDONESIA BASIC 6.0 - David Muhammad Nur; Irfan, Skom, MMSi Irfan, Skom, MMSi (Jurnal Sistem Informasi, 2010)
This scholarly writing explain the payroll system at. Amdah Indonesia that during thisprocess is done by manual. Therefore, the authors make a payroll system with using acomputerized with Visual Basic 6.0 programming language and Databases using MSAccess.Hopefully this writing has become an alternative for a company or to itsemployees who expect all the activities run by effective, efficient and coordinated.